What Does it Mean to Act Professionally? Ideas of Professionalism Within Medical, Police, and Social Work Education - Liljeholm, Maria (Professions and professionalism, 2025)
Professionalism is a crucial element of curricula in many profession-oriented higher education programmes. However, defining and working with professionalism-oriented learning objectives can be challenging. Comparative perspectives on professionalism across educational contexts are often missing. This study explores educators’ ideas on what students need to learn to effectively navigate and manage their professional practice within three professional education programmes: police, medical, and social work. The analysis captures how professionalism is portrayed in documents and interviews with teachers. The findings highlight shared ideas of professionalism across educational boundaries. The concept is described as multi-dimensional and complex, necessitating more communication about what can be expected of students and how teaching and assessment should be designed.